High-Throughput Genotyping of Salmonella enterica Serovar Typhi Allowing Geographical Assignment of Haplotypes and Pathotypes within an Urban District of Jakarta, Indonesia - Baker, Stephen (American Society for Microbiology (ASM), 2008)
High-throughput epidemiological typing systems that provide phylogenetic and genotypic information are beneficial for tracking bacterial pathogens in the field. The incidence of Salmonella enterica serovar Typhi infection in Indonesia is high and is associated with atypical phenotypic traits such as expression of the j and the z66 flagellum antigens. Utilizing a high-throughput genotyping platform to investigate known nucleotide polymorphisms dispersed around the genome, we determined the haplotypes of 140 serovar Typhi isolates associated with Indonesia. We identified nine distinct serovar Typhi haplotypes circulating in Indonesia for more than 30 years, with eight of these present in a single Jakarta suburb within a 2-year period. One dominant haplotype, H59, is associated with j and z66 flagellum expression, representing a potential pathotype unique to Indonesia. Phylogenetic analysis suggests that H59 z66(+), j(+) isolates emerged relatively recently in terms of the origin of serovar Typhi and are geographically restricted. These data demonstrate the potential of high-throughput genotyping platforms for analyzing serovar Typhi populations in the field. The study also provides insight into the evolution of serovar Typhi and demonstrates the value of a molecular epidemiological technique that is exchangeable, that is internet friendly, and that has global utility.